2018
DOI: 10.1038/s41393-018-0174-z
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drug claims following a traumatic spinal cord injury for older adults: a retrospective population-based study in Ontario, Canada

Abstract: Study designRetrospective cohort study.ObjectivesThe objectives for this study were to examine the prevalence of polypharmacy for people with traumatic spinal cord injury (SCI) following injury and to determine risk factors.SettingOntario, CanadaMethodsWe used provincial-level administrative health services data of publicly funded healthcare encounters housed at the Institute for Clinical Evaluative Sciences, Toronto, Ontario. We examined prescription medications dispensed over a 1 year period post injury for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The estimated lifetime economic burden associated with a traumatic SCI in Canada ranges from $1.47 million for a person with incomplete paraplegia to $3.03 million for one with complete tetraplegia [17]. People with SCI are high users of medications, taking between 5–14 different medications concurrently, often with complex regimens [18]. Therefore, individuals with SCI represented an ideal population of high users of medications for this study due to the chronic nature of their condition, the presence of multiple consequences of injury and the level of disability associated with an SCI [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…The estimated lifetime economic burden associated with a traumatic SCI in Canada ranges from $1.47 million for a person with incomplete paraplegia to $3.03 million for one with complete tetraplegia [17]. People with SCI are high users of medications, taking between 5–14 different medications concurrently, often with complex regimens [18]. Therefore, individuals with SCI represented an ideal population of high users of medications for this study due to the chronic nature of their condition, the presence of multiple consequences of injury and the level of disability associated with an SCI [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] As a result, treatment plans are often complex, 9,10 involving the concomitant use of multiple medications (i.e. polypharmacy), [11][12][13][14] which often include high-risk prescription drugs (e.g. opioids, benzodiazepines).…”
Section: Spinal Cord Injury and Dysfunction (Sci/d) Can Results In Permentioning
confidence: 99%
“… 26–28 Although few SCI-specific studies have investigated continuity of care on health outcomes, one contemporary study found that persons with continuity of care were less likely to partake in polypharmacy. 29 30 To this effect, to improve survival outcomes, regular, life-long specialised care is critical for the long-term management of secondary health conditions (eg, cardiovascular disease, urinary tract infections, respiratory infections and pressure ulcers) associated with premature mortality. 13 However, current evidence suggests inadequate management and support of secondary health conditions.…”
Section: Discussionmentioning
confidence: 99%